Metals, textiles and ceramics: Three lines of analysis to suggest a relationship between Santiago del Estero plain inhabitants and Tawantinsuyu - Taboada , Constanza; Angiorama , Carlos I. (Memoria Americana. Cuadernos de Etnohistoria, 2010)
This paper is based on a previous study (Angiorama y Taboada 2008) which was carried on in order to explain the existence and distribution of metal objects and valliserranas features in the province of Santiago del Estero. Now we incorporate and analyse relevant information about textiles and ceramics. Our research shows that some kind of relationship could have existed between Tawantinsuyu and certain groups from the Salado Medio. We suggest that this connection would have adopted some kind of alliance between the Empire and the local communities.